Survey of student interest in sports extracurricular at senior high school - Muhammad Teguh Prasetyo; Fatkhurrohman Fatkhurrohman (CV Rezki Media, 2022)
This study aims to determine how much students are interested in extracurricular sports at Senior High School 2 Skanto. This research is descriptive research by applying a survey technique. The sample in this study were students of Senior High School 2 Skanto, with a total of 30 students. The data collection instrument used was a questionnaire/questionnaire to measure students' interest in extracurricular activities. The technique for collecting samples is the purposive sampling method. The technique in collecting data is the method of distributing extracurricular questionnaires. The technique applied in data analysis is the percentage analysis technique by classifying answers in tabular form based on the core discussion and then presented in graphic form. The results showed students' interest in soccer extracurricular activities was higher, 88.10% than green peace extracurricular activities with 81.71%. However, the results for both of them in participation in extracurricular activities at Senior High School 2 Skanto are very high.